Q Inversion and Comparison of Influential Factors among Three Methods: CFS, SR, and AA (Communications in Computational Physics, 2020)
The goals of this study were to examine factors influencing Q inversion andto provide references for practical application. Three different methods for invertingQ values with VSP data were explored, including centroid frequency shift (CFS), spectral ratio (SR), and amplitude attenuation (AA). Comparison between the CFS and theother two methods was conducted on frequency band widths and low attenuation,wavefield components, interface interference, and thin layers. Results from severalsets of VSP modeling data indicated that the CFS method is more stable and accuratefor dealing with thin and high Q layers. Frequency band width, especially the presenceof high frequencies, influences the inversion effect of all three methods. The wider theband, the better the results. Q inversion from downgoing wavefield was very similarto that of the upgoing wavefield. The CFS method had fewer outliers or skip valuesfrom the full wavefield than the other two methods. Moreover, the applications to Qinversion for the set of field VSP data demonstrated that the Q curves from the CFSmethod coincided with the geological interpretations better than the Q curves of theother methods. Meanwhile, inverse Q filtering shifted the frequency component from25 Hz to 35 Hz. The results demonstrated that the Q curve is more sensitive to geological horizons than velocity.